Carboxylated calixarenes bind strongly to CD69 and protect CD69(+) killer cells from suicidal cell death induced by tumor cell surface ligands - Bezouska, Karel; Snajdrová, Renata; Krenek, Karel; Vancurová, Markéta; Kádek, Alan; Adámek, David; Lhoták, Pavel; Kavan, Daniel; Hofbauerová, Katerina; Man, Petr; Bojarová, Pavla; Kren, Vladimír (Bioorganic & medicinal chemistry, 2010)
We have recently identified a new class of high affinity ligands for CD69 leukocyte membrane receptor, carboxylated calixarenes. Of the three compounds investigated here, thiacalix[4]arene had the highest affinity for CD69 in direct binding assays, and proved to be the most specific inhibitor of CD69 identified so far in receptor precipitation and cellular activation experiments. Carboxylated calixarenes also proved effective at protection of CD69(high) lymphocytes from apoptosis triggered by a multivalent ligand or antibody. Thus, carboxylated calixarenes set a new paradigm for noncarbohydrate ligands for CD69 making them attractive for protection of killer cells in combined animal tumor therapies.
Keywords: Antigens, CD; lektiny typu C; Ligands; CD antigeny; Humans; ligandy; Carboxylic Acids; krysa rodu Rattus; Lectins, C-Type; kyseliny karboxylové; lidé; zvířata; kalixareny; apoptóza; Calixarenes; diferenciační antigeny T-lymfocytů; Antigens, Differentiation, T-Lymphocyte; Rats; Animals; Apoptosis